2016
DOI: 10.1007/978-3-319-28802-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Grid Cells and Spatial Maps in Entorhinal Cortex and Hippocampus

Abstract: The cortical circuit for spatial representation has multiple functionally distinct components, each dedicated to a highly specific aspect of spatial processing. The circuit includes place cells in the hippocampus as well as grid cells, head direction cells and border cells in the medial entorhinal cortex. In this review we discuss the functional organization of the hippocampal-entorhinal space circuit. We shall review data suggesting that the circuit of grid cells has a modular organization and we will discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Evidence for grid-cell-like representations in humans has been detected as well (Doeller, Barry, & Burgess, 2010). The cortical circuit for spatial representation thus has multiple functionally distinct components, each dedicated to a highly specific aspect of spatial processing (Stensola & Moser, 2016).…”
Section: Neuroanatomical Topology and Mappingmentioning
confidence: 98%
“…Evidence for grid-cell-like representations in humans has been detected as well (Doeller, Barry, & Burgess, 2010). The cortical circuit for spatial representation thus has multiple functionally distinct components, each dedicated to a highly specific aspect of spatial processing (Stensola & Moser, 2016).…”
Section: Neuroanatomical Topology and Mappingmentioning
confidence: 98%
“…An example of the inseparability of H's role in self-hood and embodiment comes from the discovery of place cells in the hippocampus and grid cells of entorhinal cortex (Stensola & Moser, 2016). This spatial location system must include H in order to allow the brain to know where its body resides in space.…”
Section: Selfhood and Othernessmentioning
confidence: 99%
“…Additionally, while many studies have investigated grid coding during free foraging tasks, a recent study found that introducing reward locations altered the structure of grid cells in medial entorhinal cortex to preferentially represent the reward location (Butler, Hardcastle, & Giocomo, 2019). More generally, other findings have suggested that the involvement of entorhinal cortex in navigation can vary based on environmental features (Barry, Ginzberg, O'keefe, & Burgess, 2012;Stensola & Moser, 2016) and behavioral demands (Rodo, Sargolini, & Save, 2017;Yoo & Lee, 2017). Together, these findings reveal that grid cell coding in the entorhinal cortex is inconsistently hexagonally symmetric, rarely static, and is flexible.…”
Section: What About Situations Involving Neural Recordings Of Grid mentioning
confidence: 99%